2011
DOI: 10.1111/j.1750-3841.2011.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

Raphasatin Is a More Potent Inducer of the Detoxification Enzymes Than Its Degradation Products

Abstract: Glucoraphasatin, the primary glucosinolate in radishes, is metabolized into an isothiocyanate (raphasatin) that has biological activity but is also unstable in an aqueous environment. Despite the instability of raphasatin, dietary exposure to radishes produced significant induction of detoxification enzymes. Understanding the chemical properties of raphasatin, both in terms of biological activity and instability, could help develop processing methods to retain the most activity from radishes, glucoraphasatin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 32 publications
(41 reference statements)
2
43
1
Order By: Relevance
“…The molecular mass of GRE was found to be m/z 434.09 with primary fragment ions of 419.12, 259.59, 275.43, 301.34 and 357.37. These figures coincided with those of the primary fragment ion of GRE previously reported (Scholl et al, 2011). contents in radish sprouts during 3 weeks after germination.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The molecular mass of GRE was found to be m/z 434.09 with primary fragment ions of 419.12, 259.59, 275.43, 301.34 and 357.37. These figures coincided with those of the primary fragment ion of GRE previously reported (Scholl et al, 2011). contents in radish sprouts during 3 weeks after germination.…”
Section: Resultssupporting
confidence: 91%
“…The molecular weight separated from the chromatogram of the shoot was m/z 418.34 with primary fragment ions of 259.00, 275.00, 301.00, and 354.09, also matching the figures from a previous study (Scholl et al, 2011).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, these findings contradict the work of Scholl et al (2011) who demonstrated that in the HepG2 cells, glucosinolate glucoraphasatin induced quinone reductase activity of significantly higher than its degradation products that were generated by addition of myrosinase into the cell culture media prior to the addition to the cells; however, in their studies much higher concentrations (50-200 µM) of the glucosinolate were employed. In other study, the methanol extract of radish sprouts containing glucosinolate glucoraphasatin demonstrated high potency in inducing quinone reductase activity in Hepa1c1c7 cells (Lee and Lee, 2006), although it is possible that other compounds in the extract were responsible for this effect.…”
Section: Discussioncontrasting
confidence: 65%
“…However, this compound has been reported to be highly unstable, with a half-life of less than 30 min [9]. Besides its instability RPS has been reported to significantly induce the expression of detoxifying enzmyes [14]. In mammals ITC are known to be metabolized in the enterocytes and the liver through the mercapturic acid pathway.…”
Section: Glucosinolate and Isothiocyanate Content In Radish Sproutsmentioning
confidence: 99%